Pengaruh User Interface dan Media Richness Instagram Terhadap Informasi PTS di Jakarta - Hidayat, Hidayat; Prihantoro, Edy (Universitas Prof. Dr. Moestopo (Beragama), 2025)
The advancement of technology and internet usage has significantly impacted various sectors, including higher education. Social media, particularly Instagram, has become a widely used platform for effective information dissemination. The Instagram account @humas.lldikti3 is utilized by the Higher Education Service Institution Region III to fulfill the information needs of private universities in Jakarta. However, the effectiveness of this information dissemination remains questionable, especially regarding user interface and media richness as key factors. This study aims to analyze the influence of the user interface and media richness of the Instagram account @humas.lldikti3 on fulfilling private university information. The research employs a quantitative method with a multiple regression analysis technique. The study involved 100 respondents who are active Instagram users and utilize the @humas.lldikti3 account as an information source. The findings reveal that the user interface positively and significantly affects information fulfillment, as does media richness. Simultaneously, these two variables also have a positive and significant influence on information fulfillment. These findings highlight the importance of user-friendly interface design and rich media in enhancing the quality of information dissemination through social media platforms.